Cytokines released from kidney cells exposed to Amphotericin B. - Bonis, Ben (My University, 2008)
A human proximal tubule kidney cell culture (HK-2) was established as a cell model for the study of Amphotericin B-induced nephrotoxicity. Exposure to deoxycholate-amphotericin B (DAMB) caused no increase in release of cytokines by the cells.
Color poster with text and tables describing research conducted by Ben Bonis, advised by Lloyd Turtinen.
Keywords: Cells--Effect of drugs on.; Amphotericin B--Toxicity.; Toxicity testing.; Cytokines.; Posters.